2005
DOI: 10.1007/s11240-004-6155-2
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium -mediated transformation of cotton (Gossypium hirsutum) using a heterologous bean chitinase gene

Abstract: Cotton (Gossypium hirsutum L., var. Coker 312) hypocotyl explants were transformed with three strains of Agrobacterium tumefaciens, LBA4404, EHA101 and C58, each harboring the recombinant binary vector pBI121 containing the chi gene insert and neomycin phosphotransferase (nptII) gene, as selectable marker. Inoculated tissue sections were placed onto cotton co-cultivation medium. Transformed calli were selected on MS medium containing 50 mg l )1 kanamycin and 200 mg l )1 cepotaxime. Putative calli were subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 38 publications
1
40
0
1
Order By: Relevance
“…These results represent a convincing confirmation of Agrobacterium-mediated transformation of cotton and show the potential of this technique for genetic engineering of Indian cotton. The frequencies of transformation obtained in this study seem to be equal to other systems of transformation (protoplast and biolistic) used to obtain transgenic cotton, although genotypic differences must be considered [9] . Selection markers mediated inheritance studies on T 1 progeny showed that the chitinase gene is transmitted to the T 1 progeny, demonstrating stable incorporation of T-DNA into the cotton nuclear DNA and the 3:1 segregation ratio suggested that the chitinase gene was integrated at a single locus.…”
Section: Expression Of Chitinasementioning
confidence: 62%
See 2 more Smart Citations
“…These results represent a convincing confirmation of Agrobacterium-mediated transformation of cotton and show the potential of this technique for genetic engineering of Indian cotton. The frequencies of transformation obtained in this study seem to be equal to other systems of transformation (protoplast and biolistic) used to obtain transgenic cotton, although genotypic differences must be considered [9] . Selection markers mediated inheritance studies on T 1 progeny showed that the chitinase gene is transmitted to the T 1 progeny, demonstrating stable incorporation of T-DNA into the cotton nuclear DNA and the 3:1 segregation ratio suggested that the chitinase gene was integrated at a single locus.…”
Section: Expression Of Chitinasementioning
confidence: 62%
“…Previously, three reports were published on transgenic cotton with chitinase gene. Those studies, they used tobacco chitinase [36] : Fungal chitinase of Trichoderma virens [37] and bean chitinase [9] to control the fungal pathogens Verticillium dahliae, Rhizoctonia solani, Alternaria macrospora and A. alternate respectively [38] . These reports are relevant to American and Turkey cotton varieties due to genotype dependent responses.…”
Section: Expression Of Chitinasementioning
confidence: 99%
See 1 more Smart Citation
“…Callus maturation was achieved on MS basal medium in duration of 2 months. Most of the published works had also reported MS based medium containing 2,4-D and kinetin as the best for callus induction Goodin, 1987 and1988a, b;Kumria et al, 2003;Choudhary et al, 2003;Haq and Zafar, 2004;Tohidfar et al, 2005;Zhao et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Transferred chitinase genes originate either from plants (Lin et al 1995, Kishimoto et al 2004, Chye et al 2005, Takashaki et al 2005, Tohidfar et al 2005, Vellicce et al 2006, Xiao et al 2007, He et al 2008, fungi (Terakawa et al 1997, Mora and Earle 2001, Kumar et al 2009, Kern et al 2010, Prasad et al 2012 or viruses (Corrado et al 2008). …”
Section: Plants Transformed With Chitinase Genesmentioning
confidence: 99%